Phase theory : an introduction - Citko, Barbara, 1970- (Cambridge : Cambridge University Press, 2014)
Phase Theory is the latest empirical and conceptual innovation in syntactic theory within the Chomskyan generative tradition. Adopting a cross-linguistic perspective, this book provides an introduction to Phase Theory, tracing the development of phases in minimalist syntax. It reviews both empirical and theoretical arguments in favor of phases, and examines the role phases play at the interface with semantics and phonology. Analyzing current phasehood diagnostics, it applies them in a systematic fashion to a broad range of syntactic categories, both phases and non-phases. It concludes with a discussion of some of the more contentious issues in Phase Theory, involving cross-linguistic variation with respect to phasehood and the dynamic versus static nature of phases.
The minimalist program -- Introducing phases -- Phasehood diagnostics -- Classic phases -- Other ph(r)ases -- Variation in phase hood -- Phases and the interfaces.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Phraseology; Minimalist theory (Linguistics); Grammar, Comparative and general -- Syntax; Generative grammar